2018
DOI: 10.1111/jifm.12095
|View full text |Cite
|
Sign up to set email alerts
|

What matters in disclosures of key audit matters: Evidence from Europe

Abstract: New regulation in the European Union has introduced the mandatory disclosure of key audit matters (KAMs) to audit reports. The EU has identified KAMs as significant risks, significant transactions or events, or significant judgments by auditors. This paper aims to determine the factors that influence the number of KAMs that auditors disclose in the main European countries under the new regulation. We predict that the litigation risk, reputation loss, auditor-client relationship, precision of accounting standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
5
31

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(153 citation statements)
references
References 64 publications
9
108
5
31
Order By: Relevance
“…Thus, H 2 is rejected. As explained by Pinto and Morais (2019), this result can be explained by the fact that the auditor's decision to disclose a KAM may be a choice between maintaining its reputation and maintaining a certain level of return. DeAngelo (1981) indicates that auditors are more likely to question their independence in relation to more important clients.…”
Section: Results Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, H 2 is rejected. As explained by Pinto and Morais (2019), this result can be explained by the fact that the auditor's decision to disclose a KAM may be a choice between maintaining its reputation and maintaining a certain level of return. DeAngelo (1981) indicates that auditors are more likely to question their independence in relation to more important clients.…”
Section: Results Analysismentioning
confidence: 99%
“…Similar to Pinto and Morais (2019), this article uses the theory of Hogarth (1980) regarding the assimilation of information in the judgement and decision-making process to identify the factors that influence the number of KAMs that auditors disclose. As stated by Pinto and Morais (2019), in the KAM disclosure process, auditors can use avoidance or confrontation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firmrelated variables include firm size (SIZE), firm risk (RISK), return on assets (ROA), quick asset ratio (QUICK), ratio of debt to total assets (DEBT), presence of a net loss in the current year (LOSS), and complexity (SEGMENTS). Extant research deems larger, leveraged, and loss-making firms more incentivized to engage in more aggressive financial reporting and to likely have more KAMs (Pinto and Morais 2019;Sierra-Garcia et al 2019). Firm risk (RISK) proxies for the firm's operating and business risk environment; number of business segments (SEGMENTS) proxies for the firm's operating complexity; and discretionary accruals (ACC RUA LS) proxy for firm's earning management practices.…”
Section: Research Model Specification For H1mentioning
confidence: 99%
“…Meanwhile, Pinto and Morais (2019) found that a higher number of business segments (complexity) and more precise accounting standards lead to the disclosure of a higher number of KAMs. They also found that a positive association exists between the audit fee and the number of KAMs disclosed.…”
Section: Literature Reviewmentioning
confidence: 99%